(untitled) (Prosiding dan Call Paper Widya Wiwaha, 2023)
This study aims to determine whether price, product quality, and service quality affect customer satisfaction. The method used in this study using a purposive sampling method. The sample in this study consisted of 50 respondents who are customers of Mool.Spdr. The technique used in this research is multiple linear regression and t test. This study shows that there is an influence of price, product quality and service quality on customer satisfaction Mool.SPDR. The results of this study indicate that the better the price, product quality, and service quality, the customer satisfaction will increase.